Otra perspectiva de la participación de los niños, niñas y adolescentes (NNA) víctimas en el sistema de justicia penal en México - Ayala Narváez, Yubia Yumiko (Archivos de criminología, seguridad privada y criminalística, 2023)
Children and adolescents who inevitably find themselves in the need to report an act of which they were victims, should know that being heard and participating in the justice process is a right they have and it is important to assert, it also serves as a mechanism of protection and crime inhibitor thereby achieving the cessation of violence, provides a sense of dignity and important resignification for their recovery, noting that the path of silence will never be the option to crime and re-victimization will never be the cost of justice.